Slowly Progressive Type 1 Diabetes following Steroid-Sensitive Relapsing Nephrotic Syndrome in Childhood: A Case Report - Masashi Kitahara; Kenji Kurata (Biomedicine Hub)
Introduction: In rare cases, idiopathic nephrotic syndrome (NS) and type 1 diabetes coexist, with diabetes typically preceding NS or presenting almost simultaneously with an acute onset requiring immediate insulin therapy. Case Presentation: We report a unique case of a 5.1-year-old male who developed idiopathic NS and experienced glycosuria during steroid treatments for relapses, initially attributed to steroid-induced hyperglycemia. At age 10.2, he developed persistent glycosuria without steroid administration, and an oral glucose tolerance test confirmed diabetes. Despite positive anti-insulinoma-associated protein-2 antibodies, the patient maintained non-insulin-dependent glycemic control until, 13 months later, rapid-onset hyperglycemia necessitated insulin therapy, leading to a diagnosis of slowly progressive type 1 diabetes (SPT1D). Conclusion: This case represents the first reported instance of steroid-sensitive relapsing NS followed by SPT1D in childhood.